Utilization of the Visiting Jogja Mobile Application as a Provider of Information Regarding Limitations of Tourism Activities During the COVID-19 Pandemic in the Special Region of Yogyakarta - Triastutiningsih, Candra (Springer Science and Business Media Deutschland GmbH, 2022)
COVID-19 pandemic has caused reduction of tourist arrival, and thus it has resulted in crisis of tourism sector in Special Region of Yogyakarta. The government has implemented health protocols in accordance to Decree of the Minister of Health No. HK.01.07/MENKES/382/2020 as an effort to revive the tourism sector while minimizing the spread of COVID-19. The information regarding the regulation can be conveyed by utilizing ICT, one of them is through Visiting Jogja Mobile Application. This study aimed to identify the provision of information on the Visiting Jogja Mobile Application regarding restrictions on tourism activities and identify the utilization of the application among people who carry out tourism activities during the COVID-19 pandemic. This study used qualitative research methods. Primary data were collected through in-depth interviews and online questionnaires. Secondary data were obtained from literature studies and browsing applications with smartphones. All of the data were analyzed by qualitative and quantitative descriptive analysis. The results show that the application provides information and helps implement 4 of the 8 health protocols through its features. Utilization of applications by tourists is still low both from system management and survey results. Therefore, branding is still needed about the application to the public. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.